2000
DOI: 10.1053/jhep.2000.17660
|View full text |Cite
|
Sign up to set email alerts
|

Loss of nuclear p53 protein in preneoplastic rat hepatocytes is accompanied by Mdm2 and Bcl-2 overexpression and by defective response to DNA damage in vivo

Abstract: Previous studies have indicated that isolated preneoplastic rat hepatocytes in vitro fail to induce nuclear p53 protein and fail to block replication in response to genotoxic compounds. This suggests that defects in the protection of genomic integrity are part of their premalignant character. In the present study, we have investigated if similar defects occur in vivo. Preneoplastic glutathione-S-transferase (GST) 7-7-positive foci were induced in male Wistar rats by diethylnitrosamine (DEN) initiation and prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
3
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
1
19
3
1
Order By: Relevance
“…It was suggested that this may facilitate clonal expansion of PNL under stress induced by DNA-damaging chemicals [Lennartsson et al, 1988]. In rats submitted to the RH model X-ray-induced genotoxic stress resulted in p53 accumulation in the cytoplasm of GST 7-7-positive PNL hepatocytes and in the nucleus of surrounding hepatocytes [Van Gijssel et al, 2000]. However, in this study the authors did not distinguish pPNL from rPNL regarding cytoplasmic p53 accumulation in contrast to our study.…”
contrasting
confidence: 95%
See 3 more Smart Citations
“…It was suggested that this may facilitate clonal expansion of PNL under stress induced by DNA-damaging chemicals [Lennartsson et al, 1988]. In rats submitted to the RH model X-ray-induced genotoxic stress resulted in p53 accumulation in the cytoplasm of GST 7-7-positive PNL hepatocytes and in the nucleus of surrounding hepatocytes [Van Gijssel et al, 2000]. However, in this study the authors did not distinguish pPNL from rPNL regarding cytoplasmic p53 accumulation in contrast to our study.…”
contrasting
confidence: 95%
“…The intensity of staining in the cytoplasm (p53 and Bcl-2) or whole cell (p65) of preneoplastic cells was classified as higher than (positive p53, Bcl-2, or p65 staining PNL) or equal to (negative p53, Bcl-2, or p65 staining PNL) the reference staining in the cytoplasm or whole cell of surrounding hepatocytes. A PNL was classified as positive for p53, Bcl-2, or p65 staining if 50% or more of the cells concerned were stained more intensively than the staining in surrounding hepatocytes [Van Gijssel et al, 2000]. To verify if the PNL were pPNL or rPNL, all the immunohistochemical evaluation analyses of p53, Bcl-2, and p65 staining were made comparing the serial histological sections with those marked for GST-P.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the early events in liver carcinogenesis is p53 overexpression, which has been detected in nodules of non-tumourous liver cirrhosis and which is considered to indicate a cellular stress response preceding manifestation of HCC (Livni et al, 1995). P53 is bound by oncoprotein MDM2 which may also contribute to hepatocarcinogenesis since MDM2 overexpression as a potential tumorigenic event was demonstrated in preneoplastic rat hepatocytes as well as in human HCC (Endo et al, 2000;Van Gijssel et al, 2000). The present study proves that MDM2 accumulation is also a feature of some regenerative nodules in human cirrhotic livers.…”
Section: Discussionmentioning
confidence: 99%